The modern directions of development of investment activities in the Republic of Kazakhstan - Romanko, E.B.; Jazykbayeva, B.K.; Kazbekov, T.B.; Mussabekova, А.О.; Mukanova , A.S. (BUKETOV BUSINESS REVIEW, 2019)
In the article strategic tasks of attraction of foreign investments into the republic, an active role of the state in attraction of foreign investments, methods of the state impact on investment processes, investment policy of Kazakhstan, investment climate, investment activity in the republic, the investment legislation of the Republic of Kazakhstan are considered. It is shown that Kazakhstan, the first of the CIS countries gained investment country rating that foreign investors are guided first of all by investment climate of Kazakhstan which is defined by independent experts and serves for the instruction on efficiency of investments in this or that country. For the implementation of investment policy of the country National investment strategy for attraction of investments is accepted by the Government of the Republic of Kazakhstan. For improvement of investment climate in Kazakhstan at the request of the head of state the national company is created. «Kazakh invest» called to become a uniform negotiator on behalf of the Government with foreign businessmen. The leading sectors and branches of economy are highlighted which are priority for attraction of new investments to which the followings are allocated: food industry, deep oil refining, gas and minerals and also mechanical engineering. Recommendations about improvement of investment climate of Kazakhstan, definition investment platforms, selection of partners are analysed; innovations within the improvement of investment climate, coordinating of the state support; activity of «Kazakh invest» investment company. Definition of concrete projects with participation of the foreign investors providing the creation of new jobs. Offers for business for the purpose of creation of new projects are revealed. In the article it is noted that the great value is attached to Kazakhstan-Chinese cooperation which is characterized by a wide range of areas of trade and economic interaction. The main source is an open dialogue with investors, improvement of infrastructure for attraction of investments. By the author the main prospects of development of investment activities in RK are defined.